The mTOR–lysosome axis at the centre of ageing - Carosi, Julian M.; Fourrier, Célia; Bensalem, Julien; Sargeant, Timothy J. (FEBS open bio, 2022)
Age‐related diseases represent some of the largest unmet clinical needs of our time. While treatment of specific disease‐related signs has had some success (for example, the effect of statin drugs on slowing progression of atherosclerosis), slowing biological ageing itself represents a target that could significantly increase health span and reduce the prevalence of multiple age‐related diseases. Mechanistic target of rapamycin complex 1 (mTORC1) is known to control fundamental processes in ageing: inhibiting this signalling complex slows biological ageing, reduces age‐related disease pathology and increases lifespan in model organisms. How mTORC1 inhibition achieves this is still subject to ongoing research. However, one mechanism by which mTORC1 inhibition is thought to slow ageing is by activating the autophagy–lysosome pathway. In this review, we examine the special bidirectional relationship between mTORC1 and the lysosome. In cells, mTORC1 is located on lysosomes. From this advantageous position, it directly controls the autophagy–lysosome pathway. However, the lysosome also controls mTORC1 activity in numerous ways, creating a special two‐way relationship. We then explore specific examples of how inhibition of mTORC1 and activation of the autophagy–lysosome pathway slow the molecular hallmarks of ageing. This body of literature demonstrates that the autophagy–lysosome pathway represents an excellent target for treatments that seek to slow biological ageing and increase health span in humans. Slowing biological ageing represents a target that could significantly increase health span and reduce the prevalence of multiple age‐related diseases. Inhibition of mTORC1 can slow ageing; however, research on how this happens is still ongoing. We discuss the bidirectional relationship between mTORC1 and its major effector, the autophagy–lysosome pathway and how this relationship can be used to address age‐related disease. Created with BioRender.com.